The effect of trace minerals on the stability of retinol acetate, cholecalciferol and selenomethionine stability within premixes - M. Concarr; I. Sinkunaite; R. Murphy (Journal of Applied Animal Nutrition)
This study compared the effect of an organic proteinate mineral source and an inorganic sulphate mineral source in relation to their effect on the stability of retinol acetate and cholecalciferol within simulated premixes, while comparing the stability of two different selenomethionine (SeMet) sources (selenium enriched yeast (SeYeast) and the chemically synthesised L-SeMet) in the presence of inorganic sulphate mineral sources within simulated premixes. Four vitamin-trace mineral premixes, two containing organic trace mineral sources in the form of proteinates and two containing inorganic trace mineral sources in the form of sulphates, were formulated so that, when added to a complete broiler feed at the appropriate inclusion rates, they contained the same amount of retinol acetate and cholecalciferol and varying levels of trace minerals (National Research Council recommended level, commonly used industry level or a reduced inclusion level). The two SeMet-trace mineral premixes were formulated to contain commonly used industry levels of vitamins and trace minerals. The two SeMet-trace mineral premixes differed in the source of SeMet. One premix contained chemically synthesised L-SeMet while the other contained SeYeast. The vitamin content of the four vitamin-trace mineral premixes was analysed after 14 and 84 days in storage by ultra-high performance liquid chromatography and the amount present within each of the premixes was compared to the quantity determined prior to storage. In general, the premixes formulated with the sulphate trace mineral source were found to have higher losses of retinol acetate and cholecalciferol than those formulated with the proteinate trace mineral source. The inclusion of the proteinate minerals at both National Research Council and reduced inclusion levels significantly (P≤0.05) increased the stability of both the vitamins when compared to the inorganic sulphate mineral sources included at commonly used industry levels. The SeMet content of the two SeMet-trace mineral premixes was analysed after 49 days in storage by high performance liquid chromatography – inductively coupled plasma mass spectrometry and the amount of SeMet present within each of the samples was compared to the quantity determined prior to storage. SeMet present within the SeYeast was found to be significantly more stable (P≤0.05) than the chemically synthesised L-SeMet.